Local stability under evolutionary game dynamics - William H. Sandholm (Theoretical Economics, 2010)
We prove that any regular ESS is asymptotically stable under any impartial pairwise comparison dynamic, including the Smith dynamic; under any separable excess payoff dynamic, including the BNN dynamic; and under the best response dynamic. Combined with existing results for imitative dynamics, our analysis validates the use of ESS as a blanket sufficient condition for local stability under evolutionary game dynamics.
Keywords: C73; 330; Evolutionary game dynamics; ESS